Critical literacies for a datafied society: academic development and curriculum design in higher education - Javiera Atenas; Leo Havemann; Cristian Timmermann (Association for Learning Technology, 2020)
Participation in democracy, in today's digital and datafied society, requires the development of a series of transversal skills, which should be fostered in higher education (HE) through critically oriented pedagogies that interweave technical data skills and practices together with information and media literacies. If students are to navigate the turbulent waters of data and algorithms, then data literacies must be featured in academic development programmes, thereby enabling HE to lead in the development of approaches to understanding and analysing data, in order to foster reflection on how data are constructed and operationalised across societies, and provide opportunities to learn from the analysis of data from a range of sources. The key strategy proposed is to adopt the use of open data as open educational resources in the context of problem and research-based learning activities. This paper introduces a conceptual analysis including an integrative overview of relevant literature, to provide a landscape perspective to support the development of academic training and curriculum design programmes in HE to contribute to civic participation and to the promotion of social justice.